On Jacobi forms of lattice index - Mocanu, Andreea (2019)
Jacobi forms arise naturally in number theory in several ways: theta series arise as functions of lattices, Siegel modular forms give rise to Jacobi forms through their Fourier-Jacobi expansion and the largest Mathieu group gives rise to semi-holomorphic Maass-Jacobi forms, for example. Jacobi forms of lattice index have applications in the theory of reflective modular forms and that of vertex operator algebras, among other areas.